2013
DOI: 10.1097/rlu.0b013e318279bf4d
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 177Lu-EDTMP in Bone Metastatic Pain Palliation in Breast Cancer and Hormone Refractory Prostate Cancer

Abstract: This study indicated that (177)Lu-EDTMP was an effective and safe treatment for palliation of metastatic bone pain in patients with prostate or breast cancer. A dose of 1295 MBq (35 mCi) was sufficient for bone pain palliation therapy, and doses as high as 2590 MBq (70 mCi) were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 17 publications
2
43
0
1
Order By: Relevance
“…EDTMP, one of the most widely used ligands, forms stable complexes with various radiometals and these complexes concentrate in the skeleton in proportion to osteoblastic activity and exhibit other favorable pharmacologic characteristics in biologic systems. Thus, 177 Lu-EDTMP has favorable physical and biologic characteristics for the treatment of painful bone metastases (15,(20)(21)(22). 177 Lu-EDTMP studies on animals have shown significant skeletal uptake within 1 h after injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTMP, one of the most widely used ligands, forms stable complexes with various radiometals and these complexes concentrate in the skeleton in proportion to osteoblastic activity and exhibit other favorable pharmacologic characteristics in biologic systems. Thus, 177 Lu-EDTMP has favorable physical and biologic characteristics for the treatment of painful bone metastases (15,(20)(21)(22). 177 Lu-EDTMP studies on animals have shown significant skeletal uptake within 1 h after injection.…”
Section: Discussionmentioning
confidence: 99%
“…153 Sm-EDTMP (mean b-energy, 233 keV; half-life, 1.9 d; g-energy, 103 keV), with its short b-range emission, has advantages over radionuclides with high b-energy in terms of reduced incidence of bone marrow suppression. 177 Lu chelated with EDTMP is a new and relatively inexpensive bone-seeking radiopharmaceutical and can be potentially useful for systemic therapy in patients with bone metastases (13)(14)(15). 177 Lu-EDTMP (maximum b-energy, 497 keV; half-life, 6.7 d, g-energy, 208 keV), with its short b-range emission and half-life of 6.7 d, may be a useful alternative to 153 Sm-EDTMP for systemic radionuclide therapy with logistical advantages due to the relatively longer half-life of 177 Lu; furthermore, 177 Lu labeling with other ligands such as DOTATATE (for neuroendocrine tumors) and prostate-specific membrane antigen (for prostatic carcinoma) make it more attractive for an active therapeutic nuclear medicine program.…”
mentioning
confidence: 99%
“…The in vivo applications of key 177 Lu radiopharmaceuticals for a variety of therapeutic procedures include peptide receptor radionuclide therapy [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], bone pain palliation [27][28][29][30][31][32][33], radiation synovectomy [34][35][36][37][38][39] and radioimmonutherapy [40][41][42][43][44][45][46]. There is a steadily expanding list of 177 Lu-labeled radiopharmaceuticals that is currently being evaluated at the preclinical research or at product development stages; these may potentially be used in vivo in humans for evaluation for radionuclide therapy [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of complete response in the bone pain palliation was between 55% and 80%. This study demonstrated that an administered activity of 1295 MBq (35 mCi) was sufficient for bone pain palliation therapy and administered activities as high as 2590 MBq (70 mCi) were well tolerated (Shinto et al, 2014;Yuan et al, 2013). Taken together the data indicated that the 177 Lu-EDTMP had an adequate bone uptake, rapid urinary excretion and prolonged retention in the bone tissue.…”
Section: Iiig 177 Lu-ethylenediaminetetramethylene Phosphonic Acid mentioning
confidence: 60%